Soap Operas for Female Micro Entrepreneur Training - Eduardo Nakasone; Máximo Torero Cullen (Inter-American Development Bank (IDB), 2014)
This paper analyzes the impact of the Strengthening Women Entrepreneurship in Peru (SWEP) program. SWEP trained female micro entrepreneurs in business management practices (such as accounting and marketing). The training, which was provided in 4- to 5-hour sessions, used soap operas and practical exercises specifically designed for the program. A field experiment was conducted among a group of micro entrepreneurs based in two Peruvian cities (Lima and Piura) to investigate whether SWEP had a positive impact on its beneficiaries. The results show that the program positively affected the adoption of business practices taught by the program. In particular, those who received the training were 4 to 6 percentage points more likely to assign themselves a fixed salary (rather than taking cash from their businesses based on personal needs) and 6 to 11 percentage points more likely to keep better records of potential business contacts. Some positive impacts were found on the adoption of bookkeeping practices (4 to 6 percentage points), although this result is not significant across all of the specifications. Although these changes in adoption rates were large compared with their baseline levels, they were rather small in absolute terms. Therefore, the study did not find any impact on average business performance, household expenditures, or women's empowerment in the household. Qualitative information suggests that micro entrepreneurs were satisfied with the training, but considered that many of the practices taught by the program were difficult to follow because of time constraints.
hdl:11319/6791
Keywords: 330